The Evolution of Collembola Higher Taxa (Arthropoda, Hexapoda) Based on Mitogenome Data - Bruno Cavalcante Bellini; Feng Zhang; Paolla Gabryelle Cavalcante de Souza; Renata Clicia dos Santos-Costa; Gleyce da Silva Medeiros; Nerivânia Nunes Godeiro (Diversity, 2022)
Mitogenomes represent useful tools for investigating the phylogeny of many metazoan clades. Regarding Collembola, the use of mitogenomics has already shown promising results, but few published works include sufficient taxon sampling to study its evolution and systematics on a broader scale. Here, we present a phylogenetic study based on the mitogenomes of 124 species from 24 subfamilies, 16 families, and four orders—one of the most comprehensive datasets used in a molecular study of Collembola evolution to date—and compare our results with the trees from recently published papers and traditional systematic hypotheses. Our main analysis supported the validity of the four orders and the clustering of Poduromorpha with Entomobryomorpha (the traditional Arthropleona). Our data also supported the split of Symphypleona s. str. into the Appendiciphora and Sminthuridida suborders, and the division of the Neelipleona into two subfamilies: Neelinae and Neelidinae subfam. nov. On the other hand, the traditional Symphypleona s. lat., Isotomoidea, and all the Isotomidae subfamilies were refuted by our analyses, indicating a need for a systematic revision of the latter family. Though our results are endorsed by many traditional and recent systematic findings, we highlight a need for additional mitogenomic data for some key taxa and the inclusion of nuclear markers to resolve some residual problematic relationships.